Pengaruh Disiplin Kerja dan Kesehatan Keselamatan Kerja (K3) Terhadap Produktivitas Kerja Karyawan Pada PT Bina Pratama Sakato Jaya Sijunjung - Kamila Rahmayati; Armiati Armiati (Jurnal Salingka Nagari, 2024)
This study's objectives are to determine the effect of work discipline and occupational health and safety on employee productivity at PT Bina Pratama Sakato Jaya, determine the effect of occupational health and safety (K3) on employee productivity, and determine the effect of work discipline on employee productivity. This study employs a quantitative methodology for its investigation of causal and associative relationships. Respondents used were 84 employees at PT Bina Pratama Sakato Jaya Sijunjung. The analysis of the data consisted of a descriptive analysis, an inductive analysis based on multiple linear regression, the testing of a hypothesis, and the testing of a determination coefficient. At PT Bina Pratama Sakato Jaya Sijunjung, the findings indicated that both work discipline and occupational health and safety have a significant positive effect on work productivity, that work discipline has a significant positive effect on work productivity, and that occupational health and safety has a significant positive effect on work productivity. Therefore, in order for the company to achieve its productivity goals in an appropriate manner, it is imperative that employees always maintain compliance in complying with every regulation. Additionally, it is hoped that the leaders of the company can keep open communication and relationships with the employees because this will have an effect on the productivity of the employees while they are at work.